Cognitive Radio for Enhancing and Efficient Spectrum Sensing in Adhoc Networks - Emimal, M; Karthika, D (International Journal of Computer Sciences and Engineering, 2025)
The Spectrum sensing strategies in CR is exhibited in this paper. There are three Spectrum sensing strategies of CR, for example, helpful, non-agreeable and impedance based discovery. Helpful and non-agreeable procedures are only transmitter location and collector recognition separately. Non helpful spectrum sensing procedures is grouped in three systems like vitality recognition, coordinated channel discovery and cyclo stationary component location. The goal of the project is to achieve performance, increase reliability and efficiency and reduces the interference. In CRN the users are classified into Licensed Primary Users and Unlicensed Secondary Users and there is no dedicated channel to send data, sensors need to negotiate with the neighbors and select a channel for data communication in CR-WSNs. This is a very challenging issue, because there is no cooperation between the PUs and SUs. PUs may arrive on the channel any time. If the PU claims the channel, the SUs have to leave the channel immediately. PU is communicating with another user, that time SU cannot communicate to PU at particular time. Here Medium access Control (MAC) protocol is proposed to improve the spectrum efficiency. Our proposed CR method helps to automatically search the users those who are free to communicate in the network, at that time Unlicensed user is automatically will change as licensed user, then it communicate to particular person.